Determining the factors associated with blood‐borne virus testing of substance misusers presenting to hospital. Issue 8 (August 2017) - Tennant, Elaine; Vollmer‐Conna, Ute; Demirkol, Apo; Post, Jeffrey J.
Abstract: Background: Diagnosing blood‐borne virus (BBV) infection is an essential first step in eliminating transmission and securing access to treatment amongst substance misusers. Aims: To determine the proportion of substance misusers presenting to hospital who undergo BBV testing and the factors influencing testing. Methods: A retrospective cross‐sectional study was performed of patients presenting to two Sydney teaching hospitals with substance misuse diagnoses between January and April 2015. Proportions tested for human immunodeficiency virus, hepatitis C and hepatitis B previously and during the index hospitalisation presentation were examined. Multivariable analysis was performed to determine factors associated with testing. Results: Of 239 patients, 47 (19.7%) had a documented BBV at baseline. Of those with unknown BBV status, 29 (12.8%) had undergone some attempt at testing during presentation; 3.1% had their hepatitis B immunity assessed. Factors associated with an increased likelihood of testing during presentation included documented injecting drug use (odds ratio (OR) 15.14; 95% confidence interval (CI) 4.21–54.50; P < 0.001), admission under a physician (OR 11.79; 95% CI 2.82–49.40; P = 0.001) and admission on a Friday (OR 4.46; 95% CI 1.28–15.48; P = 0.02). Patients who had had more than one previous admission in the preceding 6 months (OR 0.24; 95% CI 0.078–0.73; P = 0.01) or a length of stay of 1 day or less (OR 0.17; 95% CI 0.032–0.87; P = 0.033) were less likely to be tested. Conclusion: Despite the high baseline prevalence of BBV infections in the population, there were many missed opportunities for BBV testing. We found patient‐, admission‐ and clinician‐level barriers that could be addressed to enhance BBV testing uptake.